LINGKUNGAN KERJA FISIK, LINGKUNGAN KERJA NON FISIK, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI GURU SMK NEGERI 1 MANOKWARI - Dewi Fitriani; Nurlaela Nurlaela; Dirarini Sudarwadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
The research objective is to examine the effect of physical work environment, non-physical work environment and work discipline on employee performance. This type of research is quantitative. Data analysis using multiple linear regression, R2 test, t test, and F test. Respondents were teachers of SMK Negeri 1 Manokwari, using saturated sample techniques with a sample of 45 employees. The results showed that partially the physical work environment variable had no effect on performance, as evidenced by the results of the t test which showed a significance value greater than 0.05 (0.449), non-physical work environment variables did not affect performance as evidenced by the t test results indicating significant value greater than 0.05 (0.961) and the results of the t test on work discipline variables affect performance, as evidenced by a significant value smaller than 0.05 (0,000). Simultaneously that physical work environment, non physical work environment, work discipline have a significant effect on performance, as evidenced by the F test, a significant value of 0,000 is smaller than 0.05 (0,000).